2013
DOI: 10.4103/0974-8520.119684
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant activity of hydro alcoholic extract from the fruit pulp of Cassia fistula Linn.

Abstract: The present study is aimed to investigate antioxidant activity of the extracts of Cassia fistula Linn. (Leguminosae) fruit pulp. Cassia fistula Linn., a Indian Laburnum, is widely cultivated in various countries and different continents including Asia, Mauritius, South Africa, Mexico, China, West Indies, East Africa and Brazil as an ornamental tree for its beautiful bunches of yellow flowers and also used in traditional medicine for several indications. The primary phytochemical study and in vitro antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 15 publications
(14 reference statements)
1
55
0
Order By: Relevance
“…Therefore, it can be concluded that this C. fistula flower extract can reduce hyperpigmentation in human skin. Previous studies have shown that some parts of the C. fistula plant exhibited anti-oxidant activity [3638]. The aqueous and methanolic extracts of the C. fistula bark showed the free radical scavenging effect of DPPH in a dose dependent manner [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be concluded that this C. fistula flower extract can reduce hyperpigmentation in human skin. Previous studies have shown that some parts of the C. fistula plant exhibited anti-oxidant activity [3638]. The aqueous and methanolic extracts of the C. fistula bark showed the free radical scavenging effect of DPPH in a dose dependent manner [38].…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous and methanolic extracts of the C. fistula bark showed the free radical scavenging effect of DPPH in a dose dependent manner [38]. The hydroalcoholic extract of the C. fistula flower and fruit pulp showed antioxidant activity by inhibiting DPPH and hydroxyl radicals [36, 37]. Additionally, our study on the anti-oxidant activity of the butanolic extract of the C. fistula flower similarly displayed the free radical scavenging effect of DPPH and ABTS in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Further, as compared to synthetic topical products, natural products are mild, biodegradable and display low toxicity [43].…”
Section: Discussionmentioning
confidence: 99%
“…fistula L has been reported as a medicinal plant, notably in the treatment of skin and inflammatory diseases [40], particularly due to its relatively rich content of polyphenols and Vitamin C [5], which are known to highly contribute to anti-oxidant activity [43]. Interestingly, considering that the emulsion stability refers to the ability of an emulsion to resist change in its properties over time [58], no significant stability changes were observed during our study period of three months, when ANOVA statistical tests were respectively applied (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation